Humanities in the Context of Interdisciplinarity: Understanding Innovation - Žic Fuchs, Milena (2011)
This keynote adresses the importance of Humanities research in the concept of Social Innovation, especially in defining knowledge-led and risk-induced interdisciplinarity. Humanities also are the basis of developing critical and independent thought in all domains of science as well as challenging widely held assumptions and beliefs.
Projekt MZOS
ENG